2014
DOI: 10.1128/aac.01178-13
|View full text |Cite
|
Sign up to set email alerts
|

Activities of Tobramycin and Polymyxin E against Pseudomonas aeruginosa Biofilm-Coated Medical Grade Endotracheal Tubes

Abstract: Indwelling medical devices have become a major source of nosocomial infections, especially Pseudomonas aeruginosa infections, which remain the most common cause of ventilator-associated pneumonia (VAP) in neonates and children. Using medical grade polyvinyl chloride endotracheal tubes (ETTs), the activity of tobramycin and polymyxin E was quantified in a simulated prevention and treatment static time-kill model using biofilm-forming P. aeruginosa. The model simulated three clinical conditions: (i) planktonic b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 37 publications
(47 reference statements)
0
7
0
Order By: Relevance
“…Previous studies have suggested Pseudomonas aeruginosa to be a predominant colonizer of dental plaque during MV and a causative pathogen of VAP (Parker et al , 2008; Raad et al , 2011; Tarquinio et al , 2014). Current microbiological analysis relies on cost effective, readily available and reproducible microbial culture.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested Pseudomonas aeruginosa to be a predominant colonizer of dental plaque during MV and a causative pathogen of VAP (Parker et al , 2008; Raad et al , 2011; Tarquinio et al , 2014). Current microbiological analysis relies on cost effective, readily available and reproducible microbial culture.…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, ETT-associated biofilm increases the risk of upper respiratory tract infections, as well as device occlusion and wound infections, among other complications [ 7 , 8 ]. Biofilm on ETT is recognized to be one of the main causes of ventilator-associated pneumonia (VAP) [ 9 , 10 ]. The latter is commonly caused by the opportunistic pathogen Pseudomonas aeruginosa ( P. aeruginosa ) [ 11 ] .…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, combination therapy is pursued for the treatment of biofilm-related infections [ 7 , 10 , 11 ]. In particular, combinations of colistin + doripenem [ 12 , 13 ], colistin + tobramycin [ 14 , 15 ], and colistin + tigecycline [ 16 ] showed promising results under various disease conditions. Colistin, which is considered the last resort for treating the P. aeruginosa infections, is usually included in these combined treatments.…”
Section: Introductionmentioning
confidence: 99%